PRESCRIPTION AND ADEQUACY OF HEMODIALYSIS - Widiana, I Gde Raka (Medicina, 2013)
Physiologically, uremic syndrome is a pollutional phenomenone of body fluid caused by uremic substance retention due to failing kidney. Hemodialysis (HD) is a substitution therapy to replace native kidney to filter out the toxic substances. The clearance capacity can be measured using urea kinetic modeling, where urea is used as a marker. Prescription of HD will produced prescribed KT/V, namely the amount of HD doses given. On the other hand delivered KT/V is real clearance effect occurred in the body. Each component of dialysis machine can be adjusted to produce adequate delivered KT/V. This KT/V has also to be adjusted with weekly frequency of HD and residual function of the native kidney. Value of KT/V in each HD session according the consensus has to be attained in order the patient live a better life longer